Orthokeratinized odontogenic cyst - Ramakrishnan Bharathi; Gnanadeepam Santiago; Parthiban Nallaiyan (Wolters Kluwer Medknow Publications, 2014)
Odontogenic keratocyst is a cyst derived from the remnants of the dental lamina, with a biologic behavior similar to benign neoplasm and it is now designated as keratocystic odontogenic tumor (KCOT) in the new World Health Organization classification. Orthokeratinized odontogenic cyst (OOC) is a rare developmental odontogenic cyst that has been considered as a variant of KCOT until Wright (1981) defined it as a different entity. The OOC is a specific odontogenic clinicopathological entity that should be differentiated from the KCOT as it presents a completely different biological behavior. Here we present a case of OOC in a 19year-old male patient and review on its clinical and histological aspects.